Sociological and Political Constraints of Islamic Sharia Enforcement in South Sulawesi Indonesia - Ahmad Faisal; Saidah Saidah; Mukrimin Mukrimin; Zakirah Zakirah; Rizal Darwis (JURIS (Jurnal Ilmiah Syariah), 2023)
The objective of this study is to examine the challenges encountered by Islamic Sharia Enforcement Committee in South Sulawesi by analyzing the responses of charismatic ulama. Qualitative methods, such as observation, interviews, and documentation, were employed to conduct a descriptive and critical analysis. The result showed that the primary obstacle to the wider acceptance of the idea lies in the sociological rejection of ulama. Ulama opposed the plan due to their epistemological understanding of Sharia and strategic approach to advocating it within the Unitary State of the Republic of Indonesia (NKRI). Politically, they gave a substantive and cultural notion instead of formalistic and structural discourse because there are no circumstances in South Sulawesi that may force the state to grant special autonomy like in Aceh. The contemporary thinking of ulama is shaped by education and practical experience, enabling them to consider contextual factors openly. The views of the Indonesian ulama on implementing Islamic Sharia are influenced by political failures, genuine religious beliefs, and political accommodations made to address Muslim aspirations. Furthermore, the results showed a decreasing trend in the scripturalist-formalistic approach to enforcing Islamic Sharia, while the substantialistic tendency is growing in popularity.